Physicochemical properties and sensory evaluation of meat from feedlot lambs fed with wet brewery waste (Research, Society and Development, 2022)
Sheep meat presents variations in qualitative characteristics that influence consumer preference. These characteristics are influenced by ante-mortem factors, such as sex, breed, age at slaughter and feeding; and post-mortem factors, such as meat cooling and storage time and temperature. Twenty-four uncastrated Suffolk lambs were housed in individual corrals and received one of four treatments consisting of four levels of replacement of sorghum silage with wet brewery waste (WBW; 0; 33; 66 and 100% replacement). The diets were isoproteic and contained 18.8% crude protein. The weight and fat proportion in the carcass increased linearly (p≤0.05) while the muscle proportion decreased linearly (p≤0.05) as the WBW levels were increased in the diets. The proximate composition of the meat was not significantly influenced by the WBW levels (P>0.05), except for the ash content which increased linearly (p=0.0003). There was no influence (p>0.05) of the use of WBW on pH, cooking losses and lambs’ meat texture profile. Shear force decreased linearly (p≤0.05). Regarding the meat color, lightness (L*) and redness (a*) were not influenced by the inclusion of WBW. Yellowness (b*) increased linearly (p=0.0038). Regarding the attributes related to lambs’ sensory analysis, there was no effect (p> 0.05) of the inclusion of WBW in the diets. The use of WBW as a bulky food replacing sorghum silage in confined feedlot lambs diet allows the main physical-chemical characteristics related to meat quality to be kept in the normal standards obtained for ovine species.